2022
DOI: 10.26508/lsa.202101255
|View full text |Cite
|
Sign up to set email alerts
|

The value of genotype-specific reference for transcriptome analyses in barley

Abstract: It is increasingly apparent that although different genotypes within a species share “core” genes, they also contain variable numbers of “specific” genes and different structures of “core” genes that are only present in a subset of individuals. Using a common reference genome may thus lead to a loss of genotype-specific information in the assembled Reference Transcript Dataset (RTD) and the generation of erroneous, incomplete or misleading transcriptomics analysis results. In this study, we assembled genotype-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…This can be overcome by short-read sequencing data with an advantage of read depth, which permits the generation of high-confidence SJs ( Au et al, 2012 ; Kovaka et al, 2019 ; Coulter et al, 2022 ; Zhang et al, 2022 ). A recent study identified some flaws while creating RTD with a common reference genome sequence for the different genotype transcriptome sequencing data within a species ( Guo et al, 2022 ). Rice has different genotypes with high-value traits and IndicaRTD can be improved by using the genotype-specific reference genome ( Das et al, 2013 ; Roy et al, 2015 ; Shrestha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be overcome by short-read sequencing data with an advantage of read depth, which permits the generation of high-confidence SJs ( Au et al, 2012 ; Kovaka et al, 2019 ; Coulter et al, 2022 ; Zhang et al, 2022 ). A recent study identified some flaws while creating RTD with a common reference genome sequence for the different genotype transcriptome sequencing data within a species ( Guo et al, 2022 ). Rice has different genotypes with high-value traits and IndicaRTD can be improved by using the genotype-specific reference genome ( Das et al, 2013 ; Roy et al, 2015 ; Shrestha et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limitations with Illumina short reads. The transcript assemblies from short reads are often inaccurate and produce large numbers of mis-assembled transcripts and missing real transcripts [40,41]. Also, research has shown that it is difficult to reconstruct splice isoforms and quantify differential expression of isoforms using short reads [42,43], which is necessary to determine the nature of the encoded protein and in assessing a splice variant's role [32,43].…”
Section: Bioinformatic Tools Software and Computational Methods To Qu...mentioning
confidence: 99%
“…We identified 'tissue' as the main driver of transcript diversity (Figure 1b). To avoid genotypic bias introduced by using a single reference for mapping RNAseq reads 12 , we produced genotype specific reference transcript datasets (GsRTDs) for each of the twenty individuals. GsRTDs assemble a broader range of transcripts than a single reference, producing more comprehensive and accurate transcriptomes that improve transcript quantification and expression analyses [13][14][15][16] .…”
Section: A Barley Pan-transcriptomementioning
confidence: 99%